Living the gospel defending the truth - Colson, Charles W.; Beckett, John D.; Intercessors for America (Purcellville, Va. : Intercessors for America, 2006)
John D. Beckett interviews Charles Colson about his biblical worldview, the focus and role of the church, Christianity and Islam, the war on terror, the next generation's need for truth, America, knowing God and grace in crisis.
What is a Biblical worldview? -- How should the church focus -- Christianity and the church focus? -- Christianity and Islam -- Role of the church -- Worldview and public policy -- Role of democracy -- War on terror -- Next generation's need for truth --What does it mean to be human? -- America in a season of winter -- Passion to make a difference -- Paying to make a difference -- Vision for the workplpace -- Living the Gospel/Defending the truth -- Knowing God and Grace in crisis.
DVD.
Host, John D. Beckett.
Includes a bonus audio CD about John D. Beckett interviews Charles Colson.
Keywords: Apologetics -- History -- 20th century; Christianity and culture; Christianity -- 20th century